A Study on the Interaction of Digital Self-Efficacy and Peer Conformity in the Intention to Use ChatGPT Among High School Students - Wiwik Juwarini Prihastiwi; Nur Azlina Amrozi; Dzulkifli (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This study aims to examine the relationship between digital self-efficacy and peer conformity with the intention to use ChatGPT among high school students. The research employed a quantitative method using multiple regression analysis. The participants consisted of 299 high school students selected through stratified random sampling. The analysis results revealedthat digital self-efficacy had a direct and significant relationship with the intention to use ChatGPT (t = 5.305; p < 0.001), contributing an effective value of 19.9%. Peer conformity also showed a direct and significant relationship (t = 18.812; p < 0.001) with an effective contribution of 70.6%. Simultaneously, digital self-efficacy and peer conformity were significantlyrelated to the intention to use ChatGPT (F = 279.331; p < 0.001) with an R square value of 65.4%. These findings indicate that among high school students, peer conformity contributes more strongly to the intention to use ChatGPT compared to digital self-efficacy.